OPINION 33: Conservation of the Generic Name Agrobacterium Conn 1942 - Editorial Secretary (for the Judicial Commission of the International Committee on Nomenclature of Bacteria) (International Journal of Systematic and Evolutionary Microbiology, 1970)
SUMMARY The generic name Agrobacterium Conn 1942 is conserved against the name Polymonas Lieske 1928, which is placed in the list of nomina generum rejicienda. The type species is Agrobacterium tumefaciens (Smith and Townsend 1907) Conn 1942.